Hysterosalpingographic Findings of Infertile Patients Presenting to Our Reproductive Endocrinology Department: Analysis of 1,996 Cases - Inal, Zeynep O.; Inal, Hasan Ali; Altunkeser, Aysegul; Alkan, Ender; Arslan, Fatma Zeynep (Current Medical Imaging, 2019)
Background: To evaluate the hysterosalpingography (HSG) findings of women with infertility in a tertiary center located in central Turkey. Methods: A total of 1,996 patients undergoing the HSG procedure for the investigation of infertility from April 2012 to 2017 were retrospectively evaluated using the archives of the reproductive endocrinology and radiology departments. Demographic and clinical characteristics of patients with normal HSG findings (n = 1,549) and patients with abnormal HSG findings (n = 447) were compared, and the distribution of pathologies on the HSG examinations was evaluated as well. Results: There were statistically significant differences between patients with normal and abnormal HSG findings in terms of age (25.68 ± 4.54 vs. 35.87 ± 2.65, p < 0.001), type (for secondary) and duration of infertility [43.1% vs. 50.6% (p = 0.006); 7 (1-22) vs. 2 (1-12) (p < 0.001), respectively], and baseline follicle stimulating hormone and estradiol levels [7.22 ± 1.38 vs. 7.55 ± 1.42 (p < 0.001); 45.54 ± 9.92 vs. 44.40 ± 9.99 (p < 0.001), respectively]. Among a total of 1,996 HSG examinations, 447 (22.39%) showed abnormalities, of which 237 (11.87%) were associated with tubal pathologies, 163 (8.17%) with uterine pathologies, and 47 (2.35%) with a combination of both. While the most common tubal pathology was one-sided distal tubal occlusion (2.91%), the most common uterine pathology was filling defects (4.16%). Conclusion: HSG is the most commonly used, well-tolerated, low-cost, and safe radiological procedure to use for the investigation of the causes of female infertility.
Keywords: female